Establishing the availability of the mammalian genus name Antillomys and species name Antillomys rayi (Rodentia, Cricetidae) - Brace, Selina; Turvey, Samuel T.; Weksler, Marcelo; Hoogland, Menno L. P.; Barnes, Ian (THERYA, 2023)
The rodent genus name Antillomys and the species name Antillomys rayi (Cricetidae: Sigmodontinae) are unavailable, given that the publication where it originally appears did not satisfy the requirements of the International Code of Zoological Nomenclature. The names were formally described in the supplementary information (electronic online text) in Word format, and the work itself did not contain evidence that it was registered in Zoobank, as per Article 8.5.3 (amended) of the International Code of Zoological Nomenclature. In this note we establish the availability of the names Antillomys and Antillomys rayi, by fulfilling ICZNÂ´s requirements.